Law matters – assessment of country-level code implementation and sales of breastmilk substitutes in South Asia - Ching, Constance; Sethi, Vani; Nguyen, Tuan Thanh; Murira, Zivai; Shats, Katherine; Rowel, Dhammica; Ahmed, Khadheeja; Dorji, Kinley; Chakma, Indrani; Haag, Karan Courtney; Singh, Phulgendra Prasad; Khatoon, Salma; et al. (Frontiers in Public Health, 2023)
The study examines the status of implementation of the International Code of Marketing of Breast-milk Substitutes of eight countries in the South Asia region (Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka), and describes the sales value and volume of commercial milk formula (CMF) marketed as breastmilk substitutes (BMS) and baby food in four countries (Bangladesh, India, Pakistan, and Sri Lanka).Design: A mix of descriptive methods is used to assess national status of Code implementation, including a desk review of the 2022 WHO/UNICEF/IBFAN Code Status Report, systematic content analysis of national Code measures, and insights generated from the participation of key government and UNICEF/WHO actors in a regional workshop that aimed to identify each country's barriers, gaps, and the status of Code implementation. Data on the sales value and volume of CMF and baby food between 2007 to 2021 and with the prediction to 2026 in Bangladesh, India, Pakistan, and Sri Lanka were obtained from Global Data.Findings: There are major gaps in Code implementation in countries even with legal measures considered substantially aligned with the Code, such as the inadequate age range of CMF covered in the scope, insufficient safeguards against conflicts of interest in the health system, lack of warning of risks of intrinsic contamination of powdered milk formula, and an absence of effective monitoring and enforcement mechanisms. Data on CMF sales shows health facilities and pharmacies sustain the highest sales. Lower sales volume of infant formula (including special formula), compared to other CMF such as follow-up formula and growing-up milk, has been observed in three of the four countries (Bangladesh, India, and Sri Lanka). Overall, GUM, followed by baby cereals, accounted for a large portion of CMF and baby foods sales in the same three countries.Recommended actions include: 1) Closing the gaps between national measures and the Code, 2) Ensuring effective monitoring and enforcement mechanisms, 3) Strengthening conflicts of interest safeguards in the health system, 4) Tackling digital marketing, and 4) Galvanizing political support and support from in-country public health and women's rights jurist networks.